The Informal Economy of Cities in the South: The Case of Cali, Colombia (2017)
This paper analyses the dynamics of the informal economy in Cali Colombia. In particular it details the working lives and characteristics of street vendors in the main food market of the city, Santa Helena. It compares them with formal merchants in the same area and uncovers a major difference in income. Street vendors make more money. Government interventions to revitalize the area and create a linear park that requires the market’s transformation and street vendors’ relocation may be undermined due to the high earnings and expectations of street vendors.